2014
DOI: 10.2172/1120134
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Ionizing Radiation Doses Induced by High Irradiance Laser on Targets in LCLS MEC Instrument

Abstract: Comprehensive measurements for photon and neutron radiation doses generated from laserplasma interaction at SLAC's MEC laser facility have been conducted. The goals of the measurements were to:1. determine the radiation dose per laser shot as a function of laser, optic and target parameters that are relevant to the MEC laser operations, 2. validate the RPD-developed analytic model for photon dose calculations, and 3. evaluate the performance of various types of passive and active detectors in the laserinduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Bauer et al also observed at Titan that electronic-based detectors around the target chamber (i.e. ion chambers and RAD-60) did not respond during laser shots on solid target, and only passive PICs responded properly (19,20) .…”
Section: Neutron Dose At Mecmentioning
confidence: 99%
“…Bauer et al also observed at Titan that electronic-based detectors around the target chamber (i.e. ion chambers and RAD-60) did not respond during laser shots on solid target, and only passive PICs responded properly (19,20) .…”
Section: Neutron Dose At Mecmentioning
confidence: 99%